The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1021/jm201716n
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design of Novel Benzoxazinorifamycins with Potent Binding Affinity to Wild-Type and Rifampin-Resistant Mutant Mycobacterium tuberculosis RNA Polymerases

Abstract: By utilization of three-dimensional structure information of rifamycins bound to RNA polymerase (RNAP) and the human pregnane X receptor (hPXR), representative examples (2b-d) of a novel subclass of benzoxazinorifamycins have been synthesized. Relative to rifalazil (2a), these analogues generally display superior affinity toward wild-type and Rif-resistant mutants of the Mycobacterium tuberculosis RNAP but lowered antitubercular activity in cell culture under both aerobic and anaerobic conditions. Lowered affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 45 publications
3
33
0
Order By: Relevance
“…Rifalazil also exhibits dramatically reduced Cyp450 induction activity in rat and dog 12 and essentially no hPXR activation in vitro below 100 μM (MIC 90 < 4 nM) 13 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Rifalazil also exhibits dramatically reduced Cyp450 induction activity in rat and dog 12 and essentially no hPXR activation in vitro below 100 μM (MIC 90 < 4 nM) 13 .…”
Section: Introductionmentioning
confidence: 98%
“…Since the sequences and antibiotic sensitivities of E. coli and the MTB RNAPs are more similar than those of MTB and Thermus RNAPs 14 , the E. coli RNAP is a better model to study RNAP-antibiotic interactions by X-ray crystallography and for later application of derived information towards TB drug discovery. We have also synthesized a novel subclass of benzoxazinorifamycins (bxRIFs) and established that these analogues generally display superior affinity toward wild-type and Rif R mutants of the MTB RNAP relative to rifalazil 13 . In the present study, we have determined the crystal structures of E. coli RNAP σ 70 holoenzyme complexes with two selected bxRIF derivatives and determined the IC 50 values for those derivatives with the E. coli RNAP to establish a structural basis for further structure-activity relationship studies of bxRIF derivatives against RNAP.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ease with which resistance to RIF is gained by mutation at multiple sites illustrates that there are significant problems with this site for the development of antimicrobials with long therapeutic lives. While alteration of the RIF binding site does have implications for cell (69,(74)(75)(76). Cocrystal structures showed that the interactions of benzoxazinorifamycins with the RNAP ␤ fork loop II and the 3 loop may occur and may explain the improved biological activity (67,69).…”
Section: Rifamycinsmentioning
confidence: 99%
“…However, the development of RZL was suspended as it proved to be toxic in clinical trials [68]. To this end, Showalter et al are conducting an extensive SAR study of benzoxazinorifamycins, RZL derivatives, to identify a compound for further preclinical evaluation [69]. …”
Section: Repurposing: a Shortcut To Success?mentioning
confidence: 99%